Analisis Rasio Keuangan Sebagai Dasar Pengambilan Keputusan Investasi pada PT Bank Negara Indonesia (Persero) TBK Periode 2021–2025 - Mey Mey Yosilia Putri; Yasa Kanaya Tedjo; Yoyo Sudaryo; Eko Djoko Prabowo (Journal of Law, Economics, and Engineering, 2026)
This study aims to analyze the financial ratios of PT Bank Negara Indonesia (Persero) Tbk during the 2021–2025 period as a basis for investment decision-making. The research employs a quantitative approach with a descriptive method using secondary data obtained from the company's annual reports and financial statements. The analysis focuses on key financial ratios, including Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Cost to Income Ratio (CIR). The results indicate that BNI experienced consistent growth in total assets, loans, third-party funds, and equity throughout the study period. Profitability ratios remained relatively strong despite a slight decline in 2025, while CAR stayed well above the regulatory minimum and NPL continued to decrease, indicating improved asset quality. Overall, the financial ratio analysis demonstrates that BNI maintained a healthy financial condition and strong fundamentals, making the company an attractive long-term investment alternative for investors.